Patterns of Use of e-Cigarettes and Their Respiratory Effects: A Critical Umbrella Review - Giusy Rita Maria La Rosa; Riccardo Polosa; Renée O'Leary (Tobacco Use Insights)
E-cigarettes (ECs) are a well-established consumer product. To study their respiratory health effects, there is the issue of heterogenous patterns of use: concurrently with cigarette smoking (dual use), exclusive use after smoking cessation (exclusive use), or use initiated without any prior or current use of cigarettes (naïve use). Our primary goal was to synthesize the evidence on the respiratory effects of ECs use in adults, categorized by their pattern of use. Additionally, we identified the highest quality systematic reviews and critically evaluated the current literature on this topic. The review was developed with published umbrella review guidelines. The database searches were Medline, Scopus, Cochrane, Epistemonikos, LILACS, and grey literature databases. The criterion for inclusion of systematic reviews was analyses of respiratory tests from randomized controlled trials or cohort studies. Quality assessments were performed with AMSTAR2 and a checklist of reporting biases. A narrative analysis was synthesized by test method: spirometry, impulse oscillometry, breath gasses, biomarkers, and clinical serious adverse events. Twelve systematic reviews were included. The findings on respiratory functioning were statistically non-significant across all patterns of use. Reporting bias was frequently observed. Based on the current research, there is no evidence of significant change in the short or medium term in respiratory function with any pattern of ECs use. We attribute the null findings to the weaknesses of acute studies, the participants’ smoking history masking testing, and the inclusion of participants with a low frequency of use.